A Multicenter Study on the Prevalence of Eosinophilic Esophagitis and PPI-Responsive Esophageal Eosinophilic Infiltration - Okuyama, Masatsugu; Watanabe, Yoshihisa; Fujiwara, Yasuhiro; Tominaga, Kazunari; Arakawa, Tetsuo; Watanabe, Toshio; Sato, Hiroshi; Oshitani, Nobuhide; Tanaka, Fumio; Hayakawa, Tsuyoshi; Tanigawa, Tetsuya; Yamamori, Kazuki; et al. (Internal Medicine, 2012)
Objective Eosinophilic esophagitis (EoE) is diagnosed by the presence of dysphagia and intraepithelial eosinophilic infiltration of ≥15 per high-power field (HPF). EoE should be distinguished from proton pump inhibitor-responsive esophageal eosinophilic infiltration (PPI-R EEI) in patients that are responsive to PPI treatment. The aim of this study was to determine the prevalence of EoE and PPI-R EEI in Japanese patients in a multicenter study. Methods Ten hospitals participated in this study. Esophageal biopsy was performed when the patients had typical EoE symptoms or when endoscopic findings revealed a typical EoE appearance. EEI was defined as the intraepithelial eosinophilic infiltration of ≥15 per HPF. Patients with EEI received rabeprazole for 8 weeks to distinguish EoE from PPI-R EEI. Results A total of 13,634 subjects that underwent upper gastrointestinal endoscopy because of further examination or as a routine checkup were enrolled. Seventy-one (0.5%) patients suspected with EoE were examined by biopsy. A histological examination of 7 (9.9%) cases revealed EEI. Two of these 7 patients showed no symptoms and the other 5 were treated with PPI. Two (0.01%) patients were diagnosed with EoE and 3 (0.02%) with PPI-R EEI. Conclusion EoE and PPI-R EEI were rare in Japanese patients that underwent upper gastrointestinal endoscopy.